(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article reflects on the relevance of inclusive education on a global scale today, the need to provide quality education to all of them regardless of the ability and condition of the children, the research carried out in this regard. In addition, in order for children with disabilities in inclusive education to have positive mental and social development, it is necessary to live in a family and receive education in preschool educational organizations and schools, along with their peers, therefore, the need to improve the inclusive education system in preschool educational organizations is growing, and ways to improve it are revealed.